Laser cutting / Mohd Huzaifah Yusoff, Anuar Effendi Mohd Salleh and Mohd Norhisham Mustafa - Yusoff, Mohd Huzaifah; Mohd Salleh, Anuar Effendi; Mustafa, Mohd Norhisham (2000)
The laser is now approaching the end of its second decade. During the period, it has developed from what was once described as "an invention in search of an application" into one of the most important technological developments of this half-century. It has brought about a rebirth of the science and technology of optics and has led to the development of whole new industries. Viewed from almost any perspective, the laser is a remarkable device.